2001
DOI: 10.1523/jneurosci.21-16-06214.2001
|View full text |Cite
|
Sign up to set email alerts
|

Acute Neuronal Apoptosis in a Rat Model of Multiple Sclerosis

Abstract: Demyelination caused by inflammation of the CNS has been considered to be a major hallmark of multiple sclerosis (MS). Using experimental autoimmune encephalomyelitis, a model of MS, we demonstrate that an immune-mediated attack of the optic nerve is accompanied by an early degeneration of retinal ganglion cells (RGCs). The decrease of neuronal cell density was correlated with functional disabilities as assessed by visual evoked cortical potentials and electroretinogram. Visual acuity was significantly reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
145
0
4

Year Published

2002
2002
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 225 publications
(159 citation statements)
references
References 51 publications
10
145
0
4
Order By: Relevance
“…46 Recently, we reported a loss of 65% of RGCs and a severe impairment of visual function occurring in early stages of MOG-EAE. 22 In our present study, Epo treatment promoted the survival of about 50% of these neurons that underwent apoptosis in vehicletreated controls in our neuro-inflammatory animal model. Moreover, an improvement in pattern ERG recordings at day 7 after immunization as well as at day 1 of MOG-EAE was detectable in Epo-treated animals, indicating that those RGCs rescued from apoptotic neuronal cell death had preserved their electrophysiological functions.…”
Section: Discussionsupporting
confidence: 48%
See 4 more Smart Citations
“…46 Recently, we reported a loss of 65% of RGCs and a severe impairment of visual function occurring in early stages of MOG-EAE. 22 In our present study, Epo treatment promoted the survival of about 50% of these neurons that underwent apoptosis in vehicletreated controls in our neuro-inflammatory animal model. Moreover, an improvement in pattern ERG recordings at day 7 after immunization as well as at day 1 of MOG-EAE was detectable in Epo-treated animals, indicating that those RGCs rescued from apoptotic neuronal cell death had preserved their electrophysiological functions.…”
Section: Discussionsupporting
confidence: 48%
“…We have recently shown that healthy sham-immunized rats have visual acuity values of 1.3170.16 cycles per degree. 22 At the clinical onset of MOG-EAE, we observed a severe decline of specific cortical potentials in response to pattern stimulation in this previous study. In our present study, at day 7 after immunization the mean of discernable alternating bars with detectable VEP responses was located within the range of 6-12 bars (n ¼ 8 for each group) in the vehicle-treated as well as in the Epo-treated group.…”
Section: Rgc Function Determined By Erg Recordings Is Improved In Epomentioning
confidence: 56%
See 3 more Smart Citations